(untitled) (Homiletic, 2008)
This paper is the text of a keynote speech delivered at the eighth international conference of Societas Homiletica, held in Copenhagen, Denmark, 19-25 July 2008. The conference theme was “In search for meaning: does preaching make a difference?” This paper along with the response paper by Johan Cilliers, also in this issue of Homiletic, will be published along with the other papers from the conference in the forthcoming book of papers published by Societas Homiletica. Used with permission.